Korelasi Antara Kadar Asam Urat Dalam Darah dan Kristal Asam Urat Dalam Urine Pada Penderita Tuberkulosis Disertai Hiperurisemia - Nisrina Yola Khairunnisa; I Gusti Ayu Nyoman Danuyanti; Yudha Anggit Jiwantoro (Jurnal Analis Medika Biosains (JAMBS), 2022)
Tuberculosis is a contagious infectious disease caused by the bacteria Mycobacterium tuberculosis. In tuberculosis patients increased levels of uric acid in the blood. Hyperuricemia is the levels of uric acid in the blood that exceeds the normal limits. The research objective in this study was to determine the correlation between the levels of uric acid in the blood and uric acid crystals in the urine in patients with tuberculosis accompanied by hyperuricemia. The research method used in this study was survey analytic with a cross sectional approach. The research used in this study population was all patients with tuberculosis who check in Health Centers of Mataram and samples total of 24 people. Data analysis used a statistical test Spearman Rank correlation. The results showed that levels of uric acid in the blood that is 8.2 mg/dl while on uric acid crystals in urine mean 0.6/fild of view uric acid crystals. The results indicated a correlation between the levels of uric acid in the blood and uric acid crystals in the urine in patients with tuberculosis accompanied by hyperuricemia. The results of the statistical test Rank Spearman showed a p value of 0.041 < 0.05 and the results of the coefficient correlation showed a value -0.419, its mean the strength of the correlation is medium. The conclusion of this study is that the patients with tuberculosis accompanied by hyperuricemia there is a correlation between the levels of uric acid in the blood and uric acid crystals in the urine.